Wind-Solar Hybrid Power Technology for Communication Base Station - Yan Hu; Zihao Zhang; Dan Ma (Dianxin kexue)
Wind-solar hybrid power system based on the wind energy and solar energy is an ideal and clean solution for the power supply of communication base station，especially for those located at remote areas such as islands.The hybrid power system provides reliable power supply while reducing the initial investment，the maintenance costs and carbon emission.A practical and reliable designing scheme of wind-solar hybrid power technical solution was presented and analyzed for a communication base station in a remote island.